A study of brand image towards purchase intention in the Malaysia hotel industry : Purest Hotel Sungai Petani / Muhamad Najib Fahmi Md Noor - Md Noor, Muhamad Najib Fahmi (Universiti Teknologi Mara Perlis, 2020)
The research examines the direct effects of brand image, price, trust, and value on consumers' purchase intentions. Thus, it gives effect to some institutional and the organization regarding to the purchase intention the customers. Researcher has use questionnaire as the instruments to collect data from the respondents. There are about total number of 351 customers in Purest Hotel Sungai Petani represents as the population in this study. Data analysis was completed by using Statistical Package of Social Sciences (SPSS). Data collection method was conducted by distributing questionnaires to the customers who visited Purest Hotel Sungai Petani. The result shows that price and value are the critical determinants directly influencing purchase intentions. However, the impact of brand image and trust on purchase intentions is not significant. Managerial implications of these results are discussed. In addition, Purest Hotel Sungai Petani should make sure hotel price is affordable, the hotel brand is attractive, the hotel is trustworthy, the hotel will offer good value for the price to make the likelihood of customers purchase intentions is high .